Converter slagging fluxing agent based on red mud as well as preparation method and application of converter slagging fluxing agent
By mixing red mud, dust removal ash and iron oxide in a specific proportion and cold pressing, the converter slag-making flux is made, which solves the problem that red mud resources cannot be efficiently utilized, reduces the melting point of the slag and improves the flowability , realizes an efficient smelting process.
Patent Information
- Application Number
- CN202411529587.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to effectively utilize red mud and dust removal ash, resulting in the failure of efficient utilization of red mud resources, and the slag has a high melting point and poor fluidity, which affects the efficiency and effect of the smelting process.
By mixing red mud, dust removal ash and iron oxide in a specific proportion, adding adhesive and cold pressing, a converter slag-making flux is made to reduce the overall melting point of the slag and improve the fluidity of the slag.
It realizes efficient utilization of red mud resources, reduces the iron oxide content required for lime melting, improves the lime melting rate and dephosphorization effect, reduces lime consumption, and improves smelting efficiency and effect.
Smart Images

Figure CN119410855A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of iron and steel metallurgy, and in particular to a converter slag-making flux based on red mud, and a preparation method and application thereof. Background Art
[0002] Red mud is industrial waste produced by the aluminum industry. Every ton of aluminum oxide produced will produce about 1.0 to 1.8 tons of red mud. Due to the alkaline substances and other harmful components contained in red mud, whether it is landfilled or piled on land, it will cause long-term pollution to the environment and affect the quality of soil, water and air. Red mud is rich in valuable metal elements such as iron, aluminum, sodium, titanium, rare earth, gallium, etc., and its color is often red, mainly due to the high content of iron oxide. The common total iron content is 45% to 50%, and there are also small amounts of CaO, SiO2, Al2O3, K2O, Na2O and ZnO.
[0003] The dry dust removal ash of converter accounts for 16% to 20% of the steel produced per ton, which is divided into coarse ash and fine ash. The components include various oxides and impurities, mainly TFe, with a mass fraction of 43% to 65%. As shown in Table 1, the dust removal ash parameters produced by each steelmaking enterprise are slightly different. The data comes from the doctoral thesis "Study on the Gas-hard Bonding Mechanism of Cold-solidified Pellets of Converter Dust Removal Ash and Scaling of Dust Removal System". It can be seen that dust removal ash is a very valuable secondary resource for steel enterprises.
[0004] Table 1 Dust removal parameters
[0005] Enterprise units Classification TFe% CaO% MgO% ZnO% P% S% Shougang Jingtang Fine ash 46-47 15-20 - - - - Panzhihua Steel Fine ash 51.75 13.29 - - 0.125 0.058 Nippon Steel Fine ash 51.3 17.5 1.5 0.16 - - SSAB Tunnpl Fine ash 57.4 13.37 3.1 0.11 0.13 0.07 JSW Steel Fine ash 64-65 3.5-4.0 0.8-1.0 - 0.03-0.04 0.05-0.10 Baosteel Coarse ash 43.67 14.1 6.27 - - - Heavy Steel Coarse ash 54.81 18.1 6.99 1.43 0.1 0.09 Heavy Steel Fine ash 57.8 8.66 1.8 2.16 0.08 0.1 Liuzhou Iron and Steel Coarse ash 55.5 9.81 6.62 4.45 0.086 0.09 Liuzhou Iron and Steel Fine ash 58.7 5.28 0.44 3.9 0.09 0.084
[0006] For enterprises, recycling iron-containing solid waste resources such as red mud and dust ash can not only reduce production costs, but also conform to the concept of green and sustainable development. Summary of the invention
[0007] The present invention aims to overcome the deficiencies of the above-mentioned prior art and provides a red mud-based converter slag-making flux, a preparation method and application thereof. The converter slag-making flux is made of red mud and dust ash through a briquetting process, which reduces the overall melting point of the slag and improves the fluidity of the slag.
[0008] In order to achieve the above technical effects, the present invention adopts the following technical solutions:
[0009] A converter slag flux based on red mud, comprising mixed waste and a binder, wherein the mixed waste is composed of red mud, dust removal ash and iron oxide scale in a mass ratio of (45-50):(45-50):(1-5), and the mass of the binder accounts for 10wt%-14wt% of the total mass of the converter slag flux;
[0010] The total iron content of the converter slag flux is ≥50%, the compressive strength is >1500N, the moisture content is ≤1%, and the particle size range is 10mm-70mm.
[0011] In the existing red mud-based pellets, such as the red mud-based unburned pellets disclosed in Chinese patent document CN 116516149 A (application number 202310304752.6), the mass of red mud in the pellets is only 9wt%-20wt%, which contributes little to the application of red mud resources. However, in the converter slag flux provided by the present invention, red mud accounts for a relatively high proportion, realizing the efficient utilization of red mud resources.
[0012] The present invention also provides a method for preparing the above-mentioned red mud-based converter slag-making flux, comprising mixing red mud, dust ash and iron oxide scale to obtain a mixed waste, adding a binder to the mixed waste and mixing it evenly, putting it into a briquetting machine for cold pressing to obtain pellets, and then curing and drying it to obtain the red mud-based converter slag-making flux.
[0013] Preferably, in the preparation method, the total iron content in the mixed waste is ≥56%; and the curing method is to place the pellets for 48 hours to allow them to solidify naturally.
[0014] The present invention also provides the use of the red mud-based converter slag flux or the converter slag flux prepared by the preparation method in converter steelmaking.
[0015] Preferably, the converter slag-making flux is added to the converter in batches to participate in slag-making smelting, the addition amount of the converter slag-making flux is (4-16) kg / t steel, and the total addition amount of the converter slag-making flux is less than or equal to 60wt% of the total mass of the slag-making material.
[0016] Further preferably, when the converter steelmaking adopts the single slag method, the batch input is as follows:
[0017] When the blowing reaches 80 seconds, add the first batch of slag-forming materials and at the same time add 1 / 2 of the total amount of converter slag-forming flux; when the carbon-oxygen reaction is intense in the middle stage of blowing, add 1 / 4 of the total amount of converter slag-forming flux; add the remaining converter slag-forming flux 3-4 minutes before stopping blowing.
[0018] Further preferably, when the converter steelmaking adopts the slag retention method, the batch input is as follows:
[0019] When the blowing reaches 80 seconds, add 1 / 4 of the total amount of converter slag-forming flux; when the blowing reaches 2 minutes, add the first batch of slag-forming materials and at the same time add 1 / 4 of the total amount of converter slag-forming flux; when the carbon-oxygen reaction is intense in the middle stage of blowing, add 1 / 4 of the total amount of converter slag-forming flux; add the remaining converter slag-forming flux 3-4 minutes before stopping blowing.
[0020] When the carbon-oxygen reaction is intense in the middle stage, it can be judged according to the smelting process, which is generally 5 to 8 minutes of blowing.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The red mud content in the red mud-based converter slag-making flux provided by the present invention is much higher than that in the existing pellets, so that the red mud resources are efficiently utilized. At the same time, the addition of iron oxide scale controls the total iron content of the converter slag-making flux, effectively controls the overall melting point of the slag, improves the slag fluidity, reduces the iron oxide content required for lime melting, is beneficial to the rapid slaging of lime and dolomite materials, increases the lime melting rate, improves the dephosphorization effect during the smelting process, reduces the lime consumption, realizes less slag smelting, and improves the smelting efficiency and effect.
[0023] 2. The converter slag-making flux provided by the present invention has high compressive strength, is easy to transport, and facilitates accurate feeding during the smelting process through particle size control; adding to the converter can adjust the temperature rise rate in the converter, increase the mass fraction of FeO in the slag, and effectively control the mid- and late-stage drying, that is, there is no need to increase the gun position for a long time to increase iron oxide slag, reduce the steel material and temperature loss caused by drying, and greatly improve the terminal temperature and component hit rate.
[0024] 3. In the application provided by the present invention, different addition controls are performed on the converter slag-making flux according to different smelting methods. This addition mode optimizes the two operation modes, which can increase the slag-forming speed while reducing the probability of splashing, ensuring the dephosphorization rate, and improving the stability of the operation and the one-time hit rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a physical representation of the red mud-based converter slag-making flux prepared in Example 1. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with embodiments and drawings.
[0027] The raw materials used in each embodiment and comparative example are all commercially available materials in the art. For example, red mud is purchased from Shandong Weiqiao Aluminum and Electricity Co., Ltd., and the adhesive is a composite cellulose type FH series adhesive produced by Leling Chenhao Polymer Technology Co., Ltd. Technicians in this field can also select red mud and adhesives from other sources according to actual needs. The sources of other raw materials are not described here.
[0028] The contents of red mud components used in various embodiments and comparative examples are shown in the following table:
[0029] Table 2 Red mud composition content
[0030]
[0031] The contents of dust ash used in various embodiments and comparative examples are shown in the following table:
[0032] Table 3 Dust ash composition content
[0033] Substance name <![CDATA[K2O]]> <![CDATA[Na2O]]> Pb ZnO As TFe content,% 0.574 0.416 0.0217 0.189 0.0049 66.72
[0034] Example 1
[0035] A red mud-based converter slag flux, comprising a mixed waste and a binder, wherein the mixed waste consists of red mud, dust removal ash and iron oxide scale in a mass ratio of 48:50:2, and the mass of the binder accounts for 11wt% of the total mass of the converter slag flux;
[0036] In this embodiment, the red mud selected is the red mud shown in batch 1 in Table 2.
[0037] The above-mentioned red mud-based converter slag-making flux is prepared by the following method: red mud, dust ash and iron oxide scale are mixed in the above-mentioned mass ratio to prepare mixed waste, a binder is added to the mixed waste and mixed evenly, and the mixed waste is put into a briquette press for cold pressing to obtain pellets, and then the red mud-based converter slag-making flux is obtained after being placed for 48 hours and dried.
[0038] like Figure 1 As shown, the converter slag flux prepared in this embodiment has a total iron content of 51%, a compressive strength of 1570N, a moisture content of 0.32%, a particle size range of 10mm-70mm, and after measurement, some pellets have a length of φ60, a width of φ40, and a thickness of φ35.
[0039] The test method for total iron content is the test method provided by the industry standard YB / T 148-2015 "Determination of total iron content in steel slag"; the test method for compressive strength is the test method provided by GB / T 7314-2017 "Room temperature compression test method for metallic materials"; the test method for moisture content is the test method provided by GB / T 2007.6-1987 "General rules for sampling and preparation of bulk mineral products - Determination of moisture - Thermal drying method"; the particle size is directly measured by a vernier caliper.
[0040] Example 2
[0041] A converter slag-making flux based on red mud. The difference between this embodiment and Example 1 is that the mixed waste consists of red mud, dust ash and iron oxide scale in a mass ratio of 50:45:5, the red mud is the red mud shown in batch 2 in Table 2, and the preparation method is the same as that in Example 1.
[0042] The converter slag flux prepared in this embodiment has a total iron content of 54%, a compressive strength of 1555N, and a moisture content of 0.28%. The test methods of various properties are the same as those in Example 1.
[0043] Example 3
[0044] A converter slag-making flux based on red mud. The difference between this embodiment and Example 1 is that the mixed waste consists of red mud, dust ash and iron oxide scale in a mass ratio of 49:50:1, the red mud is the red mud shown in batch 3 in Table 2, and the preparation method is the same as that in Example 1.
[0045] The converter slag flux prepared in this embodiment has a total iron content of 52%, a compressive strength of 1610N, and a moisture content of 0.31%. The test methods of various properties are the same as those in Example 1.
[0046] Example 4
[0047] A converter slag flux based on red mud. The difference between this embodiment and Example 1 is that the mass of the binder accounts for 14wt% of the total mass of the converter slag flux. The red mud is the red mud shown in batch 4 in Table 2. The preparation method is the same as that in Example 1.
[0048] The converter slag flux prepared in this embodiment has a total iron content of 50%, a compressive strength of 1580N, and a moisture content of 0.30%. The test methods of various properties are the same as those in Example 1.
[0049] Experimental Example 1
[0050] Application of the red mud-based converter slag-making flux prepared in Example 1 in converter steelmaking.
[0051] In this experimental example, an experimental group and a blank group were set up. The molten iron mass in the converter in the experimental group was 128t, and the slag retention method was used for operation. The batch input of the converter slag flux was as follows:
[0052] When the blowing reaches 80 seconds, 1 / 4 of the total amount of converter slag-forming flux is added; when the blowing reaches 2 minutes, the first batch of slag-forming materials is added and at the same time, 1 / 4 of the total amount of converter slag-forming flux is added; when the carbon-oxygen reaction is intense in the middle stage of blowing, the time in this embodiment is the 6th minute of blowing, and 1 / 4 of the total amount of converter slag-forming flux is added; the remaining converter slag-forming flux is added 3 minutes before stopping blowing.
[0053] The blank group did not add converter slag-making flux.
[0054] Thirty parallel tests were set up for both the experimental group and the blank group, and the final results were averaged.
[0055] The specific molten iron conditions and the dosage of each auxiliary material for the 30 parallel tests in the experimental group are shown in the following table.
[0056] Table 4 Hot metal conditions and auxiliary material dosage
[0057]
[0058] In Table 4, the units of silicon content, carbon content and phosphorus content are all %, the unit of temperature is ℃, and the unit of auxiliary material addition is kg. Through on-site tracking, the use of slag flux, the slag is relatively active, no hanging gun blowing is required, the gun position control is slightly lower than other heats, and the TSO sample phosphorus content qualified rate is 100%, meeting the process control requirements, so the experimental furnace converter smelting process is stable, there is no return drying furnace and splashing furnace, and the control level is improved.
[0059] The converter slag sample data is shown in the following table.
[0060] Table 5 Converter slag sample data
[0061] type TFe <![CDATA[SiO2]]> CaO MgO <![CDATA[Al2O3]]> <![CDATA[TiO2]]> MnO Alkalinity R Mean value of blank group 15.26 19.99 43.67 7.40 2.83 1.00 4.59 2.20 Experimental group mean 13.07 16.67 44.54 7.74 3.28 0.87 4.47 2.67 Deviation (experimental - blank) -2.19 -3.32 0.87 0.34 0.45 -0.13 -0.12 0.47
[0062] The average content of aluminum oxide was 0.45% higher than that of the blank group, and the average content of total iron was 2.19% lower than that of the blank group. At the same time, the average basicity of the slag in the furnaces using flux was higher overall, which provided a possibility for reducing lime consumption.
[0063] Table 6 Iron-containing resource recovery data
[0064]
[0065] In Table 6, the data of each group are the average values of 30 tests, and the experimental group was tested 5 times in parallel according to the dosage in Table 4. It can be seen from the data in Table 6 that under the same conditions of producing steel grades, the cooling effect of the converter slag flux based on red mud as raw material provided by the present invention is equivalent to that of the dust ash briquette. By comparing the heats using the flux with the normal heats, the heats using the converter slag flux provided by the present invention have basically the same total amount of cold material and the same alloy consumption, and the steel material consumption is lower than the normal heat, indicating that the recovery of iron-containing resources is better than that of the heats without the flux.
[0066] Table 7 Cost comparison
[0067]
[0068] As shown in Table 7, the average amount of flux added per ton of steel is 17.80 kg / t steel, which replaces sintered ore and theoretically reduces the cost by 5.7 yuan / t steel, with obvious cost reduction effect.
[0069] Experimental Example 2
[0070] The application of the red mud-based converter slag flux prepared in Example 2 in converter steelmaking. In this experimental example, the mass of molten iron in the converter is 128t, and the single slag method is selected for operation. The specific batch input is as follows:
[0071] When the first batch of slag-forming agent is added within 90 seconds of the start of blowing, 1 / 2 of the total amount of converter slag-forming flux should be added at the same time; when the carbon-oxygen reaction is intense in the middle stage of blowing, in this experimental example, the addition time is the 7th minute of blowing, and 1 / 4 of the total amount of converter slag-forming flux is added; the remaining converter slag-forming flux is added 4 minutes before stopping blowing.
[0072] The blank group did not add converter slag-making flux.
[0073] Thirty parallel tests were set up for both the experimental group and the blank group, and the final results were averaged.
[0074] The specific molten iron conditions and the dosage of each auxiliary material for the 30 parallel tests in the experimental group are shown in the following table.
[0075] Table 8 Hot metal conditions and auxiliary material dosage
[0076]
[0077] In Table 8, the units of silicon content, carbon content and phosphorus content are all %, the unit of temperature is ℃, and the unit of auxiliary material addition is kg. Through on-site tracking, the use of slag-making flux, the slag-making time is early, the blowing slag is relatively active, the hanging gun blowing is avoided, the experimental furnace has no return drying furnace and splashing furnace, the gun position control is slightly lower than other furnaces, the phosphorus content control of the TSO sample is relatively stable, meeting the process control requirements, the converter smelting process is stable, and the carbon pulling rate of the experimental furnace is 100%.
[0078] The converter slag sample data is shown in the following table.
[0079] Table 9 Converter slag sample data
[0080] type TFe <![CDATA[SiO2]]> CaO MgO <![CDATA[Al2O3]]> <![CDATA[TiO2]]> MnO Alkalinity R Mean value of blank group 15.12 13.9 45.53 5.19 1.84 0.97 4.82 2.54 Experimental group mean 13.97 15.76 45.24 6.31 2.43 1.19 5.16 2.64 Deviation (experimental - blank) -1.15 1.86 -0.29 1.12 0.59 0.22 0.34 0.1
[0081] The average content of aluminum oxide was 0.59% higher than that of the blank group, and the average content of total iron was 1.15% lower than that of the blank group. At the same time, the average basicity of the slag in the furnace using flux was 0.1 higher, which created conditions for accelerating lime slag, improving dephosphorization rate, and stabilizing converter smelting.
[0082] Table 10 Iron-containing resource recovery data
[0083]
[0084] In Table 10, a total of 30 heats using flux and flux were compared under the condition that the raw materials of the same steel grade were basically the same. It can be seen from the data in Table 10 that the converter slag flux based on red mud as raw material provided by the present invention has the same cooling effect as the dust ash briquette. When the total amount of cold material is basically the same and the alloy consumption is basically the same, the steel material consumption of the heat using the converter slag flux provided by the present invention is lower than that of the normal heat, indicating that the recovery of iron-containing resources is better than that of the heat without flux.
[0085] Table 11 Cost comparison
[0086]
[0087] As shown in Table 11, the average amount of flux added per ton of steel is 21.7 kg / t steel, which replaces sintered ore and theoretically reduces the cost by 6.9 yuan / t steel, with a significant cost reduction effect.
Claims
1. A converter slag flux based on red mud, comprising a mixed waste and a binder, wherein the mixed waste is composed of red mud, dust ash and iron oxide scale in a mass ratio of (45-50):(45-50):(1-5), and the mass of the binder accounts for 10wt%-14wt% of the total mass of the converter slag flux; The total iron content of the converter slag flux is ≥50%, the compressive strength is >1500N, the moisture content is ≤1%, and the particle size range is 10mm-70mm.
2. A method for preparing a red mud-based converter slag flux as described in claim 1, comprising mixing red mud, dust ash and iron oxide to obtain a mixed waste, adding a binder to the mixed waste and mixing it evenly, putting it into a briquetting machine for cold pressing to obtain pellets, and then curing and drying it to obtain the red mud-based converter slag flux.
3. The preparation method according to claim 2, characterized in that: The total iron content in the mixed waste is ≥56%; the curing method is to place the pellets for 48 hours to allow them to solidify naturally.
4. An application of a converter slag-making flux based on red mud in converter steelmaking, characterized in that: The red mud-based converter slag-making flux is provided by claim 1 or the red mud-based converter slag-making flux is prepared by the preparation method described in any one of claims 2-3.
5. The use according to claim 4, characterized in that The converter slag-making flux is added into the converter in batches to participate in slag-making smelting. The addition amount of the converter slag-making flux is (4-16) kg / t steel.
6. The use according to claim 5, characterized in that And the total dosage of the converter slag-making flux is less than or equal to 60wt% of the total mass of the slag-making material.
7. The use according to claim 6, characterized in that When single slag method is used for converter steelmaking, the batch input is as follows: When the blowing reaches 80 seconds, add the first batch of slag-forming materials and at the same time add 1 / 2 of the total amount of converter slag-forming flux; when the carbon-oxygen reaction is intense in the middle stage of blowing, add 1 / 4 of the total amount of converter slag-forming flux; add the remaining converter slag-forming flux 3-4 minutes before stopping blowing.
8. The use according to claim 6, characterized in that When the slag retention method is used in converter steelmaking, the batch input is as follows: When the blowing reaches 80 seconds, add 1 / 4 of the total amount of converter slag-forming flux; when the blowing reaches 2 minutes, add the first batch of slag-forming materials and at the same time add 1 / 4 of the total amount of converter slag-forming flux; when the carbon-oxygen reaction is intense in the middle stage of blowing, add 1 / 4 of the total amount of converter slag-forming flux; add the remaining converter slag-forming flux 3-4 minutes before stopping blowing.
Citation Information
Patent Citations
Unfired pellet based on red mud as well as preparation method and application of unfired pellet
CN116516149A